IMPERIAL UNIVERSITY OF SAINT VLADIMIR TARAS SHEVCHENKO NATIONAL UNIVERSITY of KYIV: GENESIS OF MEDICAL EDUCATION AND SCIENCE (1840–2020) - MUSIENKO, N.; OSTAPCHENKO, L.; TARAN, N.; BATSMANOVA, L. (Bulletin of Taras Shevchenko National University of Kyiv. Biology, 2025)
The historical sketch of the development of medical education and science at the Taras Shevchenko National University of Kyiv for the period 1840–2020 is given.
Keywords: medicine, education, history of science